2005
DOI: 10.1211/jpp.57.9.0018
|View full text |Cite
|
Sign up to set email alerts
|

Centella asiatica accelerates nerve regeneration upon oral administration and contains multiple active fractions increasing neurite elongation in-vitro

Abstract: Axonal regeneration is important for functional recovery following nerve damage. Centella asiatica Urban herb, also known as Hydrocotyle asiatica L., has been used in Ayurvedic medicine for centuries as a nerve tonic. Here, we show that Centella asiatica ethanolic extract (100 microg mL-1) elicits a marked increase in neurite outgrowth in human SH-SY5Y cells in the presence of nerve growth factor (NGF). However, a water extract of Centella was ineffective at 100 microg mL-1. Sub-fractions of Centella ethanolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 38 publications
4
87
0
6
Order By: Relevance
“…Centella asiatica also decreases Aβ deposition in the brain. Chen et al carried out a study which suggested that Centella asiatica ethanol extract can suppress Aβ-induced neurotoxicity by enhancing the antioxidative defence system in differentiated PC12 and IMR32 cells [29,30]. Amelioration of the colchicine-induced decrease in AChE activity and inhibition of nitric oxide induced neuronal damage by asiaticoside may also explain the neuroprotective effect of Centella asiatica [31,32].…”
Section: Centella Asiaticamentioning
confidence: 99%
“…Centella asiatica also decreases Aβ deposition in the brain. Chen et al carried out a study which suggested that Centella asiatica ethanol extract can suppress Aβ-induced neurotoxicity by enhancing the antioxidative defence system in differentiated PC12 and IMR32 cells [29,30]. Amelioration of the colchicine-induced decrease in AChE activity and inhibition of nitric oxide induced neuronal damage by asiaticoside may also explain the neuroprotective effect of Centella asiatica [31,32].…”
Section: Centella Asiaticamentioning
confidence: 99%
“…Recent findings suggest that Centella asiatica has cognition-enhancing properties through its ability to protect against oxidative stress [10,11] , reduce the extent of mitochondrial damage [12] and increase axonal regeneration and neurite elongation [13] . Asiatic acid (AA) is a pentacyclic triterpene found in Centella asiatica.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous findings that Ginkgo biloba extract or EGb761 and Centella asiatica could improve the functional recovery of peripheral nerve by increasing the total number of myelinated axons in nerve (Hsu et al, 2004;Soumyanath et al, 2005), therefore, this study also determines the axonal density. Our results have also demonstrated the increase in density of axons in sciatic nerve after crush injury which in agreement with previous works.…”
Section: Discussionmentioning
confidence: 99%